Achieving person-centred health systems : evidence, strategies and challenges - Nolte, Ellen; Merkur, Sherry; Anell, Anders; European Observatory on Health Systems and Policies (Cambridge ; New York, NY : Cambridge University Press, 2020)
"The idea of person-centred health systems is widely advocated in political and policy declarations to better address health system challenges. A person-centred approach is advocated on political, ethical and instrumental grounds and believed to benefit service users, health professionals and the health system more broadly. However, there is continuing debate about the strategies that are available and effective to promote and implement 'personcentred' approaches. This book brings together the world's leading experts in the field to present the evidence base and analyse current challenges and issues. It examines 'person-centredness' from the different roles people take in health systems, as individual service users, care managers, taxpayers or active citizens. The evidence presented will not only provide invaluable policy advice to practitioners and policymakers working on the design and implementation of person-centred health systems but will also be an excellent resource for academics and graduate students researching health systems in Europe"--
The person at the centre of health systems : an introduction -- Person-centredness : exploring its evolution and meaning in the health system context -- Person-centred health systems : strategies, drivers and impacts -- Achieving person-centred health systems : levers and strategies -- Community participation in health systems development -- Patient and public involvement in research -- Listening to People : measuring views, experiences and perceptions -- Choosing providers -- Choosing payers : can insurance competition strengthen person-centred care? -- The service user as manager of care : the role of direct payments and personal budgets -- Choosing treatments and the role of shared decision-making -- The person at the centre? : the role of self-management and self-management support -- Patients' rights : from recognition to implementation.
Includes bibliographical references and index.
Keywords: Health services administration -- Europe; Patient-centered health care -- Europe; Health planning -- Citizen participation; Medical policy -- Europe; Medical care -- Europe; Health services administration; Medical care; Medical policy; Patient-centered health care; Health planning -- Citizen participation; Europe